ANALISIS KHUTBAH SYAMIYAH; MANIFESTO KEBANGKITAN UMAT ISLAM KARYA BADIUZZAMAN SAID NURSI PERSPEKTIF MEANINGS AND MEDIA - Deden Mauli Darajat (Al-Mubin, 2021)
This study states that a book can be a driving force for the revival of Muslims from adversity and backwardness. Books are a medium for the dissemination of ideas, ideas and ideals and become a force in a current of civilization development. However, the recent upheaval in Syria seems to have erased what the book wanted to achieve, namely the revival of the ummah. Manifestos are notes to achieve the main goal of the resurrection of the people. This book at least offers an idea even though the reality in Syria is that there is no revival of the people. This study was analyzed using the theory of Gill Branston and Roy Stafford in the Media Student's Book (2003:11-15) which states that (1) semiotic words or signs always start from a value structure that has been formed from society, (2) a media text always contains structure, (3) a text contains denotative and connotative meanings. The semiotic, structural, denotative/connotational meaning of this book by Said Nursi describes the message that is built based on text or symbols that have been structured in Islamic society. Second, this work is shaped by the structure that was built during the writing of the book. Third, this work can denotatively be interpreted as a manifesto of the Islamic revival as a whole. However, connotatively this work shows the desire for the revival of Islam in Syria but failed